Inclusive Regional Trade: Promoting the Economic Empowerment of Women in the BBIN Region. Issue 1 (June 2019) - Livani, Talajeh; Rizwan, Nadeem; Kathuria, Sanjay
In recent years, regional integration has gained considerable importance among policymakers in Bangladesh, Bhutan, India and Nepal (often referred to as the BBIN region). There is an understanding that enhanced intra-regional trade can be a powerful tool in accelerating economic growth and reducing poverty in the BBIN region. Tapping into this potential requires careful attention to issues of exclusion and in ensuring that women and men have equal opportunity to participate and benefit from enhanced regional trade. This article discusses challenges and opportunities for women's participation in regional trade, presents a case study of women's participation and proposes policy recommendations for inclusive intra-BBIN trade expansion. The recommendations include strengthening female-dominated sectors with potential for intra-regional trade, supporting women's transition to higher levels of trade value chains, facilitating female entrepreneurs' access to productive resources and cross-border markets, mainstreaming gender in trade policy design and implementation and adopting gender-sensitive trade facilitation measures.